Diffusion tensor imaging and tractwise fractional anisotropy statistics: quantitative analysis in white matter pathology - Mueller, Hans-Peter (BioMed Central, 2007)
BACKGROUND: Information on anatomical connectivity in the brain by measurements of the diffusion of water in white matter tracts lead to quantification of local tract directionality and integrity. METHODS: The combination of connectivity mapping (fibre tracking, FT) with quantitative diffusion fractional anisotropy (FA) mapping resulted in the approach of results based on group-averaged data, named tractwise FA statistics (TFAS). The task of this study was to apply these methods to group-averaged data from different subjects to quantify differences between normal subjects and subjects with defined alterations of the corpus callosum (CC). RESULTS: TFAS exhibited a significant FA reduction especially in the CC, in agreement with region of interest (ROI)-based analyses. CONCLUSION: In summary, the applicability of the TFAS approach to diffusion tensor imaging studies of normal and pathologically altered brains was demonstrated.